Administrative Empowerment of Heads of Academic Department Councils at the Faculty of Arts at Omar Al-Mukhtar University From the Perspective of Faculty Members - Mustafa, Salim Abd Rabbo Mahmoud; eabd alqadir, faraj alsaalihin (Tobruk University Journal of Social and Human Sciences, 2025)
This study aims to evaluate the extent to which department heads at the Faculty of Arts, Omar Al-Mukhtar University, exercise administrative empowerment from the perspective of faculty members. Adopting a descriptive-analytical methodology, the study encompassed a faculty population of 133 members, with a structured survey employed as the primary instrument for data collection. Statistical analysis was conducted using the Statistical Package for the Social Sciences (SPSS).The analysis revealed that the overall level of administrative empowerment practices within the faculty was high, with "participation in decision-making" identified as the most frequently exercised dimension, while "training" was ranked the lowest. Despite variations in the degrees of practice across dimensions, all dimensions were rated highly. The results also showed that there were no statistically significant differences between the average responses of the study sample members attributed to the variable (gender, academic qualification, academic degree). In light of these findings, the study recommends that future research investigate additional factors potentially influencing administrative empowerment. Furthermore, it advocates for further studies aimed at developing targeted training and awareness programs to enhance administrative empowerment practices within academic institutions